Temperature response hydrogel as well as preparation method and application thereof

By preparing temperature-responsive hydrogels with adjustable phase change temperature and hysteresis range, the existing smart windows are solved in the difficulty of transmittance adjustment and energy consumption in different regions and seasons, and the energy-saving and adaptable smart windows are realized Effect.

CN119219849APending Publication Date: 2024-12-31NORTHWESTERN POLYTECHNICAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411360294.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The thermosensitive hydrogel materials of existing thermochromic smart windows cannot adjust the phase change temperature, resulting in the inability to effectively adjust the transmittance in different regions and seasons, and the need for continuous energy input to maintain the state, which violates the original intention of energy-saving design.

Method used

By adding methylcellulose, N-n-propylene acrylamide monomer and acrylic monomer to the buffer solution and polymerizing under the action of a tertiary amine catalyst, a temperature response with adjustable phase change temperature and hysteresis range was prepared. Hydrogels avoid volume shrinkage problems.

Benefits of technology

It realizes a temperature-responsive hydrogel smart window that maintains a phase change state without continuous energy input. It is energy-saving and adaptable, suitable for different seasons and regions, and meets the needs of use in multiple regions all-weather and weather.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219849A_ABST
    Figure CN119219849A_ABST
Patent Text Reader

Abstract

The invention provides temperature response hydrogel as well as a preparation method and application thereof, and belongs to the technical field of hydrogel synthesis. The preparation method of the temperature response hydrogel comprises the following steps: dissolving methyl cellulose in a buffer solution with the pH value of 4.5-5.5 to obtain a methyl cellulose solution; the preparation method comprises the following steps: adding an N-n-propylacrylamide monomer and an acrylic acid monomer into a methylcellulose solution, stirring until the monomers are dissolved, adding a cross-linking agent and an initiator, adding a tertiary amine catalyst at 0-5 DEG C, and polymerizing in an anaerobic environment, and reacting with methyl cellulose, an N-n-propylacrylamide monomer and an acrylic acid monomer to obtain the temperature response hydrogel. The temperature response hydrogel prepared by the invention is small in volume change before and after phase change, the problem that actual use is influenced by volume shrinkage is avoided, and when the temperature response hydrogel is used as an intelligent window, the temperature response hydrogel has hysteresis and adjustability of phase change temperature and hysteresis range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogel synthesis, and more specifically to a temperature-responsive hydrogel and a preparation method and application thereof. Background Art

[0002] The proportion of energy consumed in buildings has gradually increased due to the increase in demand for cooling and lighting. This has not only put tremendous pressure on the environment, but also led to excessive consumption of energy resources and unstable energy supply. For buildings, reasonable indoor lighting and window layout can effectively avoid unnecessary consumption of electric lighting and heating. Smart window technology can achieve the effect of regulating sunlight entry and saving energy by filling the glass interlayer with self-regulating materials for sunlight transmittance, and has received widespread attention in recent years.

[0003] Hydrogel-based smart windows have attracted extensive attention in the research field due to their excellent comprehensive performance. Similar to traditional smart windows, the common types of hydrogel-based smart windows currently include thermal response, electric field response, and humidity response. Smart windows are usually made of thermochromic, photochromic, mechanochromic, and electrochromic materials. Among the various types of smart windows, thermochromic smart windows are the most widely studied due to their adaptive response to weather and temperature.

[0004] Although there are many studies on thermosensitive hydrogel materials for thermochromic smart windows, the regulation of hydrogel smart windows is a single state regulation, and a certain temperature only corresponds to a certain value of transmittance, which cannot form the bionic memory advantage brought by hysteresis hydrogels, and cannot overcome the situation in which some sunlight weakens and causes the temperature to drop in reality. It requires continuous input of electrical energy, thermal energy or other energy to maintain a specific transmittance, such as an opaque shading state, to adjust the indoor temperature. However, the color-changing smart windows designed to save energy require continuous consumption of electrical energy or other energy to maintain the color-changing state of the smart windows, which contradicts the original design intention and seriously limits its practical application.

[0005] CN114672043A discloses a synthesis method and application of PNIPAm-HPC temperature-sensitive smart hydrogel. The phase change temperature of the smart window refers to the physical or chemical change of the material at a specific temperature, thereby changing the light transmittance or thermal resistance of the window. However, the temperature of the hydrogel phase change is not adjustable and cannot be applied to different regions. CN117106205A discloses a dual-network structure temperature-sensitive hydrogel, a preparation method and its application in the field of smart windows. The hydrogel uses a strong acid to adjust the pH, which is highly corrosive. The volume changes greatly before and after the phase change, and the volume shrinkage is not conducive to the actual use. Summary of the invention

[0006] In response to the above problems, the present invention provides a temperature-responsive hydrogel and a preparation method and application thereof. The temperature-responsive hydrogel prepared by the present invention has a small volume change before and after the phase change, thus avoiding the problem of volume shrinkage affecting actual use. When used as a smart window, it has hysteresis and adjustability of the phase change temperature and hysteresis range.

[0007] The first object of the present invention is to provide a method for preparing a temperature-responsive hydrogel, comprising the following steps:

[0008] dissolving methyl cellulose in a buffer solution having a pH value of 4.5 to 5.5 to obtain a methyl cellulose solution;

[0009] N-propyl acrylamide monomer and acrylic acid monomer are added to a methyl cellulose solution, stirred until dissolved, and then a cross-linking agent and an initiator are added. Then, a tertiary amine catalyst is added at 0°C to 5°C, and polymerization is performed in an anaerobic environment. During the polymerization process, the carbon-carbon double bond of the cross-linking agent is broken and reacts with the methyl cellulose, N-propyl acrylamide monomer and acrylic acid monomer to obtain a temperature-responsive hydrogel.

[0010] The pH of the buffer solution is 4.5, 5 or 5.5, etc.; the temperature for adding the tertiary amine catalyst is 0°C, 1°C, 2°C, 3°C, 4°C or 5°C, etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0011] The added amount of the crosslinking agent is 1.5% to 2.7% of the total weight of the methyl cellulose, the N-propyl acrylamide monomer and the acrylic acid monomer.

[0012] For example, the amount of crosslinking agent added is 1.5%, 1.7%, 1.9%, 2.1%, 2.3%, 2.5%, 2.7% of the total mass of methylcellulose, N-n-propyl acrylamide monomer and acrylic acid monomer, but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable. Increasing the amount of crosslinking agent added can prevent volume change during phase change.

[0013] In a preferred embodiment of the present invention, the added amount of the crosslinking agent is 1.5% of the total mass of the methyl cellulose, the N-n-propyl acrylamide monomer and the acrylic acid monomer.

[0014] In a preferred embodiment of the present invention, the mass ratio of methyl cellulose, N-n-propyl acrylamide monomer and acrylic acid monomer is 80-90:171-250:21-26.3; for example, the mass ratio of methyl cellulose, N-n-propyl acrylamide monomer and acrylic acid monomer is 80:171:21, 80:171:22, 80:171:23, 80:171:24, 80:171:25, 80:171:26.3, 85:171:21, 90:171:21, 80:200:21, 80:250:22, 80:250:26.3, 90:200:21, 90:250:22, 90:250:26.3, etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable. It is understandable that the increase of monomers, that is, the increase of solid content, will improve the mechanical properties of the hydrogel.

[0015] In a preferred embodiment of the present invention, the ratio of methyl cellulose to buffer is 80 mg to 90 mg:1.6 g; for example, the ratio of methyl cellulose to buffer is 80 mg:1.6 g, 82 mg:1.6 g, 84 mg:1.6 g, 86 mg:1.6 g, 88 mg:1.6 g or 90 mg:1.6 g, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0016] In a preferred embodiment of the present invention, the polymerization reaction is carried out at room temperature for 12 h to 14 h, for example, the polymerization time is 12 h, 12.5 h, 13 h, 13.5 h, 14 h, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0017] In a preferred embodiment of the present invention, the volume ratio of acrylic acid monomer to tertiary amine catalyst is 4-5:7-8, and the volume ratio of acrylic acid monomer to tertiary amine catalyst is 4:7, 4:7.5, 4:8, 4.5:7, 4.5:7.5, 4.5:8, 5:7, 5:7.5, 5:8, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0018] In a preferred embodiment of the present invention, the amount of initiator added is 1% to 1.8% of the total mass of methyl cellulose, N-n-propyl acrylamide monomer and acrylic acid monomer. For example, the amount of initiator added is 1%, 1.2%, 1.4%, 1.6%, 1.8% and the like of the total mass of methyl cellulose, N-n-propyl acrylamide monomer and acrylic acid monomer, but is not limited to the listed values. Other values ​​not listed within the above numerical range are also applicable. It is understandable that an increase in the amount of initiator added will shorten the polymerized molecular chain, reduce the molecular weight, and reduce the toughness. A decrease in the amount of initiator added will lengthen the polymerized molecular chain. Too little initiator added will result in failure of polymerization.

[0019] The second object of the present invention is to provide a temperature-responsive hydrogel prepared by the above preparation method.

[0020] The third object of the present invention is to provide application of the above-mentioned temperature-responsive hydrogel in smart windows.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) The present invention uses a buffer solution to adjust the pH, thereby avoiding the corrosiveness of strong acid in adjusting the pH. Then, N-propyl acrylamide monomer, acrylic acid monomer, and methyl cellulose are added as raw materials. Under the catalytic action of a tertiary amine catalyst, a catalytic initiator generates free radicals, which initiate a polymerization reaction of N-propyl acrylamide monomer, acrylic acid monomer, and methyl cellulose. During the polymerization process, the carbon-carbon double bond of the crosslinking agent is broken, and the crosslinking agent reacts with methyl cellulose, N-propyl acrylamide monomer, and acrylic acid monomer to obtain a temperature-responsive hydrogel. N-propyl acrylamide monomer is used for temperature response. As a monomer, the low transmittance of the prepared hydrogel is more in line with the actual use temperature. At the same time, by adding a crosslinking agent of 1.5% to 2.7% of the total mass of methyl cellulose, N-propyl acrylamide monomer, and acrylic acid monomer, the problem of volume shrinkage before and after the phase change of traditional polyacrylamide hydrogel is solved. Methyl cellulose and acrylic acid are used in combination to increase the critical solution temperature of the hydrogel under the condition of pH 4.5-5.5, so that the phase transition temperature and hysteresis width of the prepared hydrogel change, thereby making the prepared temperature-responsive hydrogel have hysteresis.

[0023] (2) The three-network temperature-responsive hydrogel prepared by the chemical cross-linking method of the present invention is well applied to smart windows. When used as a smart window, the temperature-responsive hydrogel prepared by the present invention has hysteresis and adjustability. The temperature hysteresis of the smart window means that after reaching the critical solution temperature (Lower Critical Solution Temperature, LCST), the temperature can still maintain the phase change state within a certain temperature range without the need for continuous energy input to maintain it, which is energy-saving; and adjustability means that the phase change temperature and hysteresis range have adjustable functions. The temperature response hysteresis brings more excellent energy-saving functions to smart windows. Only the initial heat input is required to meet the phase change steady state of the hydrogel. No continuous heat input is required, and it can meet the use at any time of the day. The adjustable temperature hysteresis further expands the application scope of the present invention, and meets the characteristics of customized use according to different seasons of use, longitude and latitude, personal preferences, etc. The combination of the two performances can achieve the advantages of all-weather availability and all-season multi-regional adaptability.

[0024] The temperature-responsive hydrogel smart window prepared by the present invention has a hysteresis characteristic, which is similar to the memory mechanism of intelligent organisms. This characteristic enables the window to maintain two different sunlight adjustment states at the same temperature, which can effectively deal with practical problems. For example, due to changes in the position of the sun, traditional windows may not be able to continuously reduce the light, resulting in indoor temperature fluctuations; however, the temperature-responsive hydrogel smart window prepared by the present invention can efficiently utilize energy through its adjustable hysteresis characteristics. It can respond to external thermal stimuli to maintain the desired state without the need for continuous additional energy supply, so it is superior to the hydrogel smart window without hysteresis characteristics in terms of energy utilization efficiency.

[0025] (3) The hydrogel prepared by the present invention has the following advantages when used as a smart window: (a) In the hot summer, it effectively blocks sunlight and maintains a suitable indoor temperature without any external energy input, so it has good energy saving performance. (b) The smart window can adjust the phase transition temperature by adjusting the pH, so it can be applied to different seasons. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The flowchart of the preparation of hydrogel prepolymer solution.

[0027] Figure 2 The reaction mechanism diagram of hydrogel.

[0028] Figure 3 Flow chart of the preparation of hydrogel smart window.

[0029] Figure 4 This is a scanning image of (NPAm-co-AAc)-g-MC prepared in Example 1.

[0030] Figure 5 This is a scanning image of (NPAm-co-AAc)-g-MC prepared in Example 2.

[0031] Figure 6 Infrared spectra of different samples.

[0032] Figure 7 is the transmittance of the temperature-responsive hydrogel smart window prepared in Example 4 during the heating and cooling process, wherein: Figure 7 From left to right, the a's in the figure are the transmittances corresponding to 29℃~34℃ during the heating process. Figure 7 From left to right in the graph, b indicates the transmittance corresponding to 29℃~34℃ during the cooling process.

[0033] Figure 8 The permeability curves of (NPAm-co-AAc)-g-MC prepared at different pH values; wherein a represents a pH value of 4, b represents a pH value of 4.5, c represents a pH value of 5, and d represents a pH value of 5.5.

[0034] Fig. 9 This is the infrared blocking rate curve of (NPAm-co-AAc)-g-MC prepared at different pH values; where a is a pH value of 4, b is a pH value of 4.5, c is a pH value of 5, and d is a pH value of 5.5. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] It should be noted that methyl cellulose is denoted as MC, and the molecular weight of the methyl cellulose used in the present invention is 454.5; N-propyl acrylamide is denoted as NPAm; N-isopropyl acrylamide is denoted as NIPAM; acrylic acid is denoted as (Acrylic acid) AAc; N,N-methylenebisacrylamide is denoted as MBAA; ammonium persulphate is denoted as APS; and N,N,N',N'-tetramethylethylenediamine is denoted as TEMED.

[0037] A method for preparing a temperature-responsive hydrogel, such as Figure 1 As shown, the following steps are included:

[0038] dissolving methylcellulose in a buffer solution having a pH of 4.5-5.5 to obtain a methylcellulose solution;

[0039] N-propyl acrylamide monomer and acrylic acid monomer are added to methyl cellulose solution, stirred until dissolved, and then a cross-linking agent and an initiator are added. Then, a tertiary amine catalyst is added at 0°C to 5°C, and polymerization is performed in an anaerobic environment to obtain a temperature-responsive hydrogel.

[0040] In the preparation of the temperature-responsive hydrogel, N-propyl acrylamide monomer, acrylic acid monomer, and methyl cellulose are used as raw materials, and a crosslinking agent, an initiator, and a tertiary amine catalyst are added. Figure 2 As shown, after the one-dimensional cross-linking agent reacts, the double bonds break and connect with other molecules to form a three-dimensional network structure, which makes the hydrogel have strong stability and response sensitivity, and can also improve the reusability; it should be noted that Figure 2 Here, x1, x2, y1 and y2 refer to repeating units.

[0041] In the present invention, N-propyl acrylamide monomer is used for temperature response, and methylcellulose and acrylic acid are used in combination, so that the prepared hydrogel has pH response so that the phase transition temperature and hysteresis width change, thereby making the hydrogel have hysteresis. Specifically, below LCST, the intermolecular interaction between the main chains of methylcellulose can form stable aggregates, which provides the necessary conditions for achieving significant volume changes. At a pH value of 4.5, due to the deprotonation of some PAAc repeating units, the main chain of the temperature-responsive hydrogel has stronger hydrophilicity. The hydrophilic main chain promotes the hydration of the polymer chain and inhibits the aggregation of the polymer, thereby leading to an increase in LCST. During the cooling process, the thermal behavior of the temperature-responsive hydrogel prepared with NIPAm as a monomer or the temperature-responsive hydrogel prepared with NPAm as a monomer is different from that observed during the heating process. Even at a temperature below the LCST observed during heating, the volume of the temperature-responsive hydrogel prepared with NIPAm as a monomer remains unchanged. Even if the sample is kept at 45°C, no significant change in volume is observed after 10 hours.

[0042] It is understandable that, in the preparation of the present invention, the pH of the buffer solution is 4.5-5.5. This is because when the pH is too low, acrylic acid cannot be dissociated, and when the pH is too high, it exceeds the dissociation constant of AAC, the degree of dissociation is large, the hydrophilicity increases, and the phase transition temperature increases, which is not conducive to actual use.

[0043] The temperature-responsive hydrogel prepared by the present invention can be used in smart windows, such as Figure 3 As shown, the application of hydrogels includes two methods:

[0044] (i) Use a syringe to inject the prepared hydrogel prepolymer solution into two glass plates separated by a 1 mm thick rubber gasket. Seal the injection port with tape to prevent the liquid from flowing out during vacuuming. Finally, place it in a vacuum drying oven and polymerize it for 12 to 14 hours.

[0045] (ii) Separate two pieces of glass with a side length of 18 cm with a hollow butyl rubber with a thickness of 2 mm and a frame width of 1 cm and clamp them with a clamp. Then select the needle of a 5mL syringe with a smaller capacity and insert it into the glass through the rubber ring. Slowly extract the air inside until you feel a slight resistance. Next, use a 10mL syringe to slowly push the prepolymer solution prepared under ice bath conditions into the glass interlayer through the hole for extracting air and allow it to completely occupy the entire glass interior. After the injection is completed, apply a dense layer of waterproof yellow vaseline around the glass and wrap the sealing film around the glass several times. Finally, place the sealed glass in a vacuum tank and let it stand for 8 hours under a vacuum environment to obtain a sample of the hydrogel-based smart window.

[0046] Example 1

[0047] Step 1: Dissolve 80 mg of methylcellulose in 1.6 g of acetic acid and sodium acetate buffer solution with a pH of 4.5, heat to 90°C and let stand for 1 hour to obtain a suspension with white floccules. Then, stir at room temperature for 1 hour and slowly cool it to room temperature. After stirring, let stand at 4°C overnight to obtain a viscous, uniform and transparent methylcellulose solution, which is recorded as MC solution.

[0048] Step 2: Measure 194 μL NPAM and 20 μL AAc and dissolve them in 1.6 g MC solution. Ultrasonic dispersion was performed for 1 h to fully dissolve them.

[0049] Step 3: Add 720 μL of 1 wt % MBAA aqueous solution and 100 μL of 5 wt % APS aqueous solution and continue stirring for 20 minutes.

[0050] Step 4: After stirring, transfer the mixture to an ice-water bath at 0°C. After the solution is completely cooled, add 30 μL of TEMED and continue stirring for 5 minutes. Next, introduce nitrogen gas into the solution to remove oxygen dissolved in the water, and obtain a hydrogel prepolymer solution.

[0051] Step 5: Place the hydrogel prepolymer solution in a vacuum drying oven and polymerize it at room temperature for 12 hours to obtain a temperature-responsive hydrogel.

[0052] Example 2

[0053] Step 1: Dissolve 80 mg of methylcellulose in 1.6 g of acetic acid and sodium acetate buffer solution at pH = 5, heat to 90°C and let stand for 1 hour to obtain a suspension with white floccules. Then, stir at room temperature for 1 hour and slowly cool to room temperature. After stirring, let stand at 4°C overnight to obtain a viscous, uniform and transparent methylcellulose solution, which is recorded as MC solution.

[0054] Step 2: Measure 194 μL NPAM and 20 μL AAc and dissolve them in 1.6 g MC solution. Ultrasonic dispersion was performed for 1 h to fully dissolve them.

[0055] Step 3: Add 720 μL of 1 wt % MBAA aqueous solution and 100 μL of 5 wt % APS aqueous solution and continue stirring for 20 minutes.

[0056] Step 4: After stirring, transfer the mixture to an ice-water bath at 0°C. After the solution is completely cooled, add 30 μL of TEMED and continue stirring for 5 minutes. Next, introduce nitrogen gas into the solution to remove oxygen dissolved in the water, and obtain a hydrogel prepolymer solution.

[0057] Step 5: Place the hydrogel prepolymer solution in a vacuum drying oven and polymerize at room temperature for 12 hours to obtain a temperature-responsive hydrogel, which is recorded as (NPAm-co-AAc)-g-MC.

[0058] Example 3

[0059] Step 1: Dissolve 80 mg of methylcellulose in 1.6 g of acetic acid and sodium acetate buffer solution with a pH of 5.5, heat to 90°C and let stand for 1 hour to obtain a suspension with white floccules. Then, stir at room temperature for 1 hour and slowly cool it to room temperature. After stirring, let stand overnight at 4°C to obtain a viscous, uniform and transparent methylcellulose solution, which is recorded as MC solution.

[0060] Step 2: Measure 194 μL NPAM and 20 μL AAc and dissolve them in 1.6 g MC solution. Ultrasonic dispersion was performed for 1 h to fully dissolve them.

[0061] Step 3: Add 720 μL of 1 wt % MBAA aqueous solution and 100 μL of 5 wt % APS aqueous solution and continue stirring for 20 minutes.

[0062] Step 4: After stirring, transfer the mixture to an ice-water bath at 0°C. After the solution is completely cooled, add 30 μL of TEMED and continue stirring for 5 minutes. Next, introduce nitrogen gas into the solution to remove oxygen dissolved in the water, and obtain a hydrogel prepolymer solution.

[0063] Step 5: Place the hydrogel prepolymer solution in a vacuum drying oven and polymerize it at room temperature for 12 hours to obtain a temperature-responsive hydrogel.

[0064] Example 4

[0065] Step 1: Dissolve 80 mg of methylcellulose in 1.6 g of acetic acid and sodium acetate buffer solution with a pH of 4.7, heat to 90°C and let stand for 1 hour to obtain a suspension with white floccules. Then, stir at room temperature for 1 hour and slowly cool it to room temperature. After stirring, let stand at 4°C overnight to obtain a viscous, uniform and transparent methylcellulose solution, which is recorded as MC solution.

[0066] Step 2: Measure 194 μL NPAM and 20 μL AAc and dissolve them in 1.6 g MC solution. Ultrasonic dispersion was performed for 1 h to fully dissolve them.

[0067] Step 3: Add 720 μL of 1 wt % MBAA aqueous solution and 100 μL of 5 wt % APS aqueous solution and continue stirring for 20 minutes.

[0068] Step 4: After stirring, transfer the mixture to an ice-water bath at 0°C. After the solution is completely cooled, add 30 μL of TEMED and continue stirring for 5 minutes. Next, introduce nitrogen gas into the solution to remove oxygen dissolved in the water, and obtain a hydrogel prepolymer solution.

[0069] Step 5: Place the hydrogel prepolymer solution in a vacuum drying oven and polymerize it at room temperature for 12 hours to obtain a temperature-responsive hydrogel.

[0070] Example 5

[0071] Step 1: Dissolve 90 mg of methylcellulose in 1.6 g of acetic acid and sodium acetate buffer solution at pH = 5, heat to 90°C and stand for 1 hour to obtain a suspension with white floccules. Then, stir at room temperature for 1 hour and slowly cool to room temperature. After stirring, stand at 4°C overnight to obtain a viscous, uniform and transparent methylcellulose solution, which is recorded as MC solution.

[0072] Step 2: Dissolve 250 mg NPAM and 25 μL AAc in 1.6 g MC solution and disperse by ultrasonic for 1 h to fully dissolve.

[0073] Step 3: Add 989 μL of 1 wt % MBAA aqueous solution and 132 μL of 5 wt % APS aqueous solution and continue stirring for 20 minutes.

[0074] Step 4: After stirring, transfer the mixture to an ice-water bath at 5°C. After the solution is completely cooled, add 40 μL of TEMED and continue stirring for 5 minutes. Next, introduce nitrogen into the solution to remove oxygen dissolved in the water, and obtain a hydrogel prepolymer solution.

[0075] Step 5: Place the hydrogel prepolymer solution in a vacuum drying oven and polymerize it at room temperature for 13 hours to obtain a temperature-responsive hydrogel.

[0076] Example 6

[0077] Step 1: Dissolve 85 mg of methylcellulose in 1.6 g of acetic acid and sodium acetate buffer solution at pH = 5, heat to 90°C and let stand for 1 hour to obtain a suspension with white floccules. Then, stir at room temperature for 1 hour and slowly cool to room temperature. After stirring, let stand at 4°C overnight to obtain a viscous, uniform and transparent methylcellulose solution, which is recorded as MC solution.

[0078] Step 2: Dissolve 200 mg NPAM and 23 μL AAc in 1.6 g MC solution and disperse by ultrasonic for 1 h to fully dissolve them.

[0079] Step 3: Add 618 μL of 1 wt % MBAA aqueous solution and 93 μL of 5 wt % APS aqueous solution and continue stirring for 20 minutes.

[0080] Step 4: After stirring, transfer the mixture to an ice-water bath at 3°C. After the solution is completely cooled, add 38 μL of TEMED and continue stirring for 5 minutes. Next, introduce nitrogen gas into the solution to remove oxygen dissolved in the water, and obtain a hydrogel prepolymer solution.

[0081] Step 5: Place the hydrogel prepolymer solution in a vacuum drying oven and polymerize it at room temperature for 14 hours to obtain a temperature-responsive hydrogel.

[0082] Comparative Example 1

[0083] Step 1, 80 mg of methyl cellulose was dissolved in 1.6 g of acetic acid and sodium acetate buffer solution with pH = 4, heated to 90 ° C and allowed to stand for 1 hour to obtain a suspension with white floccules. After that, it was stirred at room temperature for 1 hour and slowly cooled to room temperature. After stirring, it was allowed to stand at 4 ° C overnight to obtain a viscous, uniform and transparent methyl cellulose solution of different pH, which was recorded as MC solution.

[0084] Step 2: 194 mg NPAM and 20 μL AAc were dissolved in 1.6 g MC solution and ultrasonically dispersed for 1 h to fully dissolve.

[0085] Step 3: Add 720 μL of 1 wt % MBAA aqueous solution and 100 μL of 5 wt % APS aqueous solution and continue stirring for 20 minutes.

[0086] Step 4: After stirring, transfer the mixture to an ice-water bath at 0°C. After the solution is completely cooled, add 30 μL of TEMED and continue stirring for 5 minutes. Next, introduce nitrogen gas into the solution to remove oxygen dissolved in the water, and obtain a hydrogel prepolymer solution.

[0087] Step 5: Place the hydrogel prepolymer solution in a vacuum drying oven and polymerize it at room temperature for 12 hours to obtain a temperature-responsive hydrogel.

[0088] Comparative Example 2

[0089] Step 1: Measure 20 μL AAc and dissolve it in 1.6 g aqueous solution. Ultrasonic dispersion is performed for 5 minutes and stirring is performed for 20 minutes to fully dissolve it.

[0090] Step 2: Add 720 μL of 1 wt % MBAA aqueous solution and 100 μL of 5 wt % APS aqueous solution and continue stirring for 20 minutes.

[0091] Step 3: After stirring, transfer the mixture to an ice-water bath at 0°C. After the solution is completely cooled, add 30 μL of TEMED and continue stirring for 5 minutes. Next, introduce nitrogen into the solution to remove oxygen dissolved in the water, and obtain a hydrogel prepolymer solution.

[0092] Step 4: Place the hydrogel prepolymer solution in a vacuum drying oven and polymerize it at room temperature for 12 hours to obtain a temperature-responsive hydrogel, which is recorded as P(Acc).

[0093] Comparative Example 3

[0094] Step 1: 194 mg of NPAM was dissolved in 1.6 g of aqueous solution, ultrasonically dispersed for 5 minutes and stirred for 20 minutes to fully dissolve.

[0095] Step 2: Add 720 μL of 1 wt % MBAA aqueous solution and 100 μL of 5 wt % APS aqueous solution and continue stirring for 20 minutes.

[0096] Step 3: After stirring, transfer the mixture to an ice-water bath at 0°C. After the solution is completely cooled, add 30 μL of TEMED and continue stirring for 5 minutes. Next, introduce nitrogen into the solution to remove oxygen dissolved in the water, and obtain a hydrogel prepolymer solution.

[0097] Step 4: Place the hydrogel prepolymer solution in a vacuum drying oven and polymerize it at room temperature for 12 hours to obtain a temperature-responsive hydrogel, which is recorded as P(NPAm).

[0098] Comparative Example 4

[0099] Step 1: Dissolve 80 mg of methylcellulose in 1.6 g of acetic acid and sodium acetate buffer solution at pH = 5, heat to 90°C and let stand for 1 hour to obtain a suspension with white floccules. Then, stir at room temperature for 1 hour and slowly cool to room temperature. After stirring, let stand at 4°C overnight to obtain a viscous, uniform and transparent methylcellulose solution, which is recorded as MC solution.

[0100] Step 2: Dissolve 380 mg NIPAM and 20 μL AAc in 1.6 g MC solution, disperse by ultrasound for 5 minutes and stir for 20 minutes to fully dissolve.

[0101] Step 3: Add 720 μL of 1 wt % MBAA aqueous solution and 100 μL of 5 wt % APS aqueous solution and continue stirring for 20 minutes.

[0102] Step 4: After stirring, transfer the mixture to an ice-water bath at 0°C. After the solution is completely cooled, add 35 μL of TEMED and continue stirring for 5 minutes. Next, introduce nitrogen into the solution to remove oxygen dissolved in the water, and obtain a hydrogel prepolymer solution.

[0103] Step 5: Place the hydrogel prepolymer solution in a vacuum drying oven and polymerize it at room temperature for 12 hours to obtain a temperature-responsive hydrogel.

[0104] The temperature-responsive hydrogel prepared by the present invention is characterized and tested below.

[0105] Figure 4 This is a scan of the temperature-responsive hydrogel prepared in Example 1. Figure 5 This is a scanning image of the temperature-responsive hydrogel prepared in Example 3. It can be seen that the internal structure of the freeze-dried hydrogel at 25°C and pH values ​​of 4.5 and 5.5 was observed by scanning electron microscopy. Figure 4 and Figure 5 The typical network structure of the hydrogel is shown in Figure 2, which is similar to that of normal hydrogels. Figure 4 It can be seen from the figure that when the pH value is 4.5, the polymer chains curl up and the holes in the cross-linked network are larger; Figure 5 It can be seen that at pH 5.5, the polymer chains stretch and the pores become smaller. This shows that although the PNPAm chains of the hydrogel are hydrophilic at 25°C, as the pH value increases from 4.5 to 5.5, the PAAc chains change from hydrophobic to hydrophilic, thereby increasing the overall hydrophilicity of the hydrogel. This also indirectly indicates that when the pH value exceeds the pKa of AAc, the phase transition temperature (LCST) of the hydrogel will increase.

[0106] The present invention characterizes the components and molecular structure of the hydrogel by Fourier transform infrared spectroscopy. Figure 6This is the Fourier transform infrared spectrum of Example 2. For the hydrogel PAAc, the characteristic peak at 3393cm-1 corresponds to the stretching vibration of the hydroxyl group (-OH); the characteristic peak at 1700cm-1 is the stretching vibration peak of the carbonyl group (-C=O). For the hydrogel PNIPAm, the characteristic peaks at 3286cm-1 and 1540cm-1 are the stretching vibration peaks of the amide (-NH), and the characteristic peak at 1637cm-1 is the stretching vibration peak of the carbonyl group (-C=O). For MC, the characteristic peak at 3419cm-1 is the stretching vibration peak of the hydroxyl group (-OH), and the characteristic peak at 1050cm-1 is the stretching vibration peak of the alkoxy group (-CO). In the hydrogel P (MC-NPAm-co-AAc), the FTIR spectrum shows the characteristic functional groups of PAAc, PNPAm and MC. The characteristic peaks at 3430cm-1 and 1050cm-1 correspond to the stretching vibration peaks of the hydroxyl (-OH) and alkoxy (-CO) groups on the MC molecule, respectively; the characteristic peaks at 3282cm-1, 1540cm-1 and 1636cm-1 correspond to the stretching vibration peaks of the amide (-NH) and carbonyl (-C=O) groups on PNPAm, respectively. The slight shift of these characteristic peaks can be attributed to the intermolecular hydrogen bonding. The above results show that the MC molecules were successfully grafted onto the polymer chains PAAc and PNPAm, indicating the successful preparation of P(NPAm-co-AAc)-g-MC.

[0107] The temperature-responsive hydrogel prepared by the present invention is used in a smart window. Specifically, the prepared hydrogel prepolymer solution is injected into two glass plates separated by a 1 mm thick rubber gasket using a syringe. The injection port is sealed with adhesive tape to prevent the liquid from flowing out during vacuuming. It is placed in a vacuum drying oven and polymerized at room temperature for 12 hours to obtain a temperature-responsive hydrogel smart window, and then the transmittance and infrared blocking rate of the temperature-responsive hydrogel smart window are tested.

[0108] Figure 7 is the transmittance of the temperature-responsive hydrogel smart window prepared in Example 4, Figure 7 From left to right, the a's in the figure are the transmittances corresponding to 29℃~34℃ during the heating process. Figure 7 From left to right in the figure b, the transmittances corresponding to 29°C to 34°C during the cooling process are shown. It can be clearly observed that different transmittances are observed at the same temperature during the heating and cooling processes, and there is an obvious difference in the transmittances at 31°C to 32°C, which fully reflects the hysteresis of the temperature-responsive hydrogel prepared by the present invention.

[0109] The temperature-responsive hydrogel smart windows prepared under pH conditions of 4, 4.5, 5, and 5.5 in Comparative Example 1 and Examples 1 to 3 were tested for transmittance and infrared blocking rate. Figure 8 and Fig. 9The results show that the lowest temperatures for the hydrogel smart window to reach zero transmittance and 100% infrared blocking rate are 34°C, 37°C, and 43°C, respectively. This is because when the pH value is 4.5, the polymer chains curl up and the cross-linked network pores are larger; Figure 5 It can be seen that at pH 5.5, the polymer chains stretch and the pores become smaller. This shows that although the PNPAm chains of the hydrogel are hydrophilic at 25°C, as the pH value increases from 4.5 to 5.5, the PAAc chains change from hydrophobic to hydrophilic, thereby increasing the overall hydrophilicity of the hydrogel. This also indirectly indicates that when the pH value exceeds the pKa of AAc, the LCST of the hydrogel will increase.

[0110] Moreover, the lowest temperature at which the temperature-responsive hydrogel smart window prepared in Comparative Example 4 reaches zero transmittance and 100% UV blocking rate is T=42°C. Comparing Comparative Example 4 with Example 2, the monomer used in Comparative Example 4 is NIPAM, and the monomer used in Example 2 is NPAm. The hydrophobic force of one methyl group connected to the methylene group on NPAm is stronger than the hydrophobic force of two methyl groups connected to the methylene group of NIPAM, and the side group provides a greater hydrophobic effect, so that the hysteresis range is larger at a lower temperature.

[0111] For the temperature-responsive hydrogel prepared in Example 2, when the pH of the MC solution was 5, the lower critical solution temperature of the hydrogel increased from 32°C to 46°C, and the transmittance reached a minimum value at nearly 50°C. During the cooling process, the volume of the hydrogel sample remained unchanged until the temperature dropped to around 41°C and then returned to its initial state. At this time, the hysteresis interval of the hydrogel sample was 5°C.

[0112] Compared with the hysteresis interval of 2°C when the pH value of the MC solution is 4.5, the hysteresis interval increases by 2.5 times. In addition, when the pH of the MC solution drops to 4, the hydrogel system hardly exhibits any hysteresis performance. This is because the solution pH is less than the dissociation constant (pKa) value of acrylic acid, which also means that the acrylic acid monomer hardly dissociates under this condition. The lower phase transition temperature will also lead to the weakening of the hydrophobic interaction between the MC molecular chains, thereby causing the disappearance of the hysteresis performance of the hydrogel.

[0113] For the hydrogel prepared in Comparative Example 1, when the pH value is equal to 4, the phase transition temperature of the hydrogel has almost no significant change. During the heating process, the volume of the sample suddenly changes at around 21°C and quickly reaches the minimum value. During the cooling process, the volume of the hydrogel sample remains unchanged until it returns to the initial value at around 19°C. Therefore, under this pH condition, the NPAM-MC hydrogel system has a hysteresis range of about 2°C.

[0114] Compared with the low pH environment, the phase transition behavior of the sample was significantly improved at pH 5. The phase transition temperature was increased from nearly 20°C to 37°C. In addition, during the cooling process, a hysteresis range of nearly 10 degrees can be clearly observed. The volume of the sample was always stably maintained at a smaller size until the temperature dropped to 25°C.

[0115] The temperature range in temperate regions in summer is generally between 36°C and 41°C. Therefore, hydrogels with a low LCST system under an ambient pH of 5 can adapt well to the climatic characteristics of temperate regions due to their moderate phase transition temperature and large hysteresis range. However, smart windows have some disadvantages, such as fragility, water loss, volume shrinkage, and delayed temperature response, and the temperature at which low transmittance is reached is usually higher than the human body's comfortable temperature. In the present invention, by using NPAm hydrogel, its low transmittance is more consistent with the actual use temperature, and at the same time, the problem of volume shrinkage before and after the phase change of ordinary PNIPAm hydrogel is solved by adding an appropriate amount of cross-linking agent. This high-performance temperature-responsive hydrogel provides an impetus for the further development of the thermochromic smart window area, and also provides a new idea for the design of energy-saving materials.

[0116] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0117] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a temperature-responsive hydrogel, characterized in that: The following steps are involved: dissolving methyl cellulose in a buffer solution having a pH value of 4.5 to 5.5 to obtain a methyl cellulose solution; N-propyl acrylamide and acrylic acid monomers are added to a methyl cellulose solution, stirred until dissolved, and then a cross-linking agent and an initiator are added. Then, a tertiary amine catalyst is added at 0°C to 5°C, and polymerization is performed in an anaerobic environment. During the polymerization process, the carbon-carbon double bond of the cross-linking agent is broken and reacts with the methyl cellulose, N-propyl acrylamide monomer and acrylic acid monomer to obtain a temperature-responsive hydrogel. The added amount of the crosslinking agent is 1.5% to 2.7% of the total weight of the methyl cellulose, the N-propyl acrylamide monomer and the acrylic acid monomer.

2. The method for preparing a temperature-responsive hydrogel according to claim 1, characterized in that: The added amount of the crosslinking agent is 1.5% of the total weight of the methyl cellulose, the N-n-propyl acrylamide monomer and the acrylic acid monomer.

3. The method for preparing a temperature-responsive hydrogel according to claim 1, characterized in that: The mass ratio of methyl cellulose, N-n-propyl acrylamide monomer and acrylic acid monomer is 80-90:171-250:21-26.

3.

4. The method for preparing a temperature-responsive hydrogel according to claim 1, characterized in that: The ratio of methylcellulose to buffer is 80mg-90mg:1.6g.

5. The method for preparing a temperature-responsive hydrogel according to claim 1, characterized in that: The polymerization reaction takes 12 to 14 hours at room temperature.

6. The method for preparing a temperature-responsive hydrogel according to claim 1, characterized in that: The volume ratio of acrylic acid monomer to tertiary amine catalyst is 4-5:7-8.

7. The method for preparing a temperature-responsive hydrogel according to claim 1, characterized in that: The added amount of the initiator is 1% to 1.8% of the total weight of the methyl cellulose, the N-n-propyl acrylamide monomer and the acrylic acid monomer.

8. The method for preparing a temperature-responsive hydrogel according to claim 1, characterized in that: The crosslinking agent is N,N-methylenebisacrylamide, and the initiator is ammonium persulfate.

9. A temperature-responsive hydrogel prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the temperature-responsive hydrogel according to claim 9 in a smart window.

Citation Information

Patent Citations

  • Synthesis method and application of temperature-sensitive intelligent hydrogel based on PNIPAm-HPC

    CN114672043A

  • Temperature-sensitive hydrogel with dual-network structure, preparation method and application of temperature-sensitive hydrogel in field of preparation of intelligent windows

    CN117106205A